Proportion of preschool-aged children meeting the Canadian 24-Hour Movement Guidelines and associations with adiposity: results from the Canadian Health Measures Survey - Jean-Philippe Chaput; Rachel C. Colley; Salomé Aubert; Valerie Carson; Ian Janssen; Karen C. Roberts; Mark S. Tremblay (BMC, 2017)
Abstract Background New Canadian 24-Hour Movement Guidelines for the Early Years have been released in 2017. According to the guidelines, within a 24-h period, preschoolers should accumulate at least 180 min of physical activity (of which at least 60 min is moderate-to-vigorous physical activity), engage in no more than 1 h of screen time, and obtain between 10 and 13 h of sleep. This study examined the proportions of preschool-aged (3 to 4 years) Canadian children who met these new guidelines and different recommendations within the guidelines, and the associations with adiposity indicators. Methods Participants were 803 children (mean age: 3.5 years) from cycles 2-4 of the Canadian Health Measures Survey (CHMS), a nationally representative cross-sectional sample of Canadians. Physical activity was accelerometer-derived, and screen time and sleep duration were parent-reported. Participants were classified as meeting the overall 24-Hour Movement Guidelines if they met all three specific time recommendations for physical activity, screen time, and sleep. The adiposity indicators in this study were body mass index (BMI) z-scores and BMI status (World Health Organization Growth Standards). Results A total of 12.7% of preschool-aged children met the overall 24-Hour Movement Guidelines, and 3.3% met none of the three recommendations. A high proportion of children met the sleep duration (83.9%) and physical activity (61.8%) recommendations, while 24.4% met the screen time recommendation. No associations were found between meeting individual or combined recommendations and adiposity. Conclusions Very few preschool-aged children in Canada (~13%) met all three recommendations contained within the 24-Hour Movement Guidelines. None of the combinations of recommendations were associated with adiposity in this sample. Future work should focus on identifying innovative ways to reduce screen time in this population, and should examine the associations of guideline adherence with health indicators other than adiposity.